High-sensitivity refractive index-based microring resonator all-optical sensor with Fano resonance spectrum - Azrisham, Nurul Fathinah; Hairol Aman, Mohammad Amirul; Nazmi, Ahmad Nadzimuddin; Ahmad Noorden, Ahmad Fakhrurrazi (Institut Fizik Malaysia, 2024)
A compact high sensitivity refractive index-based all-optical sensor has garnered significant attention due to its ability to measure small changes in the optical index of refraction. In this work, sensitivity enhancement of refractive index-based microring resonator (MRR) was achieved by integrating the circulation and the interferometric resonance through the Fano resonance. The asymmetric Fano resonance was demonstrated by the incorporation of two air holes in the bus waveguide. The system was developed based on the utilization of the scattering matrix approach and the optical transfer function (OTF). Three different configurations of MRR have been analyzed and compared in this research study. The analysis of the spectrum was performed by considering the wavelength shift of the spectrum due to minimal changes in refractive indices of the order of 10-5 RIU. By optimizing the ring radius, distance between the air holes and the length of MRR, a high sensitivity enhancement of 19.11% by the all-pass racetrack Fano MRR configuration was obtained.